Auditable messages with hash chain in instant messaging apps - Komo, Andrea E.; Simplicio Jr., Marcos A. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais Estendidos do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg_estendido.2024.241723, 2024)
Instant messaging applications have been used as corporate tools, so the messages exchanged in these systems have been used as negotiation records. However, by design, most of such apps do not provide any verification feature to confirm the integrity of the conversations. Analyses show that it is possible to surreptitiously modify records in popular apps like WhatsApp and Telegram. Aiming this issue, this work proposes a message structure based on hash chain, to ensure the integrity and the possibility to audit conversations. Besides, we propose a design with selective disclosure to improve privacy during audits, and this solution is architecture-independent, so it can be integrated with any instant message app.